Answer stated as:
a'(x)=(18-x^2)^1/2 - x^2/(18-x^2)^1/2
The Attempt at a Solution
Having trouble with this solution. The chain rule states that f(x)g(x) = f'(x)g(x)+g'(x)f(x) so the first term in the solution is obviously (18-x^2)^1/2.
Where I run into problems is the second term with the numerator being x^2 when I thought it should only be x. Simplifying the problem into f(x)=(18-x^2)^1/2 the chain rule states it the derivative should be 1/2(18-x^2)(0-2x)=-x/(18-x^2)^1/2. Am I wrong or is the stated solution wrong?